Powertrain Conversion of a Small Agricultural Tractor from Diesel Engine to Permanent Magnet Synchronous Motor - Yaacob, Ahmad Zaki; Jamaluddin, Muhammad Herman; Shukor, Ahmad Zaki; Mansor, Muhd Ridzuan (International Journal of Robotics and Control Systems, 2025)
This paper presents the powertrain conversion of a small diesel-powered tractor into an electric tractor or electric off-road vehicle (EORV), offering a cost-effective alternative to purchasing a new electric model, which may be financially challenging for small-scale farmers. Given that electricity is generally cheaper than diesel fuel in Malaysia, the conversion approach aims to reduce long-term operational costs while maintaining or improving performance. The primary contribution of this work is a systematic and practical method for electric tractor conversion. The process begins with analysing the existing performance and operational requirements of the diesel tractor, followed by the selection of suitable components—namely, the electric motor, battery cells, and other associated systems. These components are then integrated into the tractor, and initial testing was performed. A speed run test was conducted to evaluate the power capability of the converted tractor. Results indicate that the electric motor delivers higher power and speed compared to the original diesel engine. The onboard energy monitoring device recorded a noticeable current spike and voltage sag during acceleration, as expected. The motor power was calculated from the recorded voltage and current data. The data show that the motor output exceeds the rated power of the original engine, suggesting that the system can handle higher loads. Some challenges encountered during the conversion process include the high initial cost, limited availability of components that meet performance requirements, and technical challenges in ensuring the durability and efficiency of the modified drivetrain. In conclusion, further testing under various load conditions is necessary to fully evaluate energy consumption and system performance in real agricultural environments.